2021
DOI: 10.14309/ajg.0000000000001148
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Characteristics and Pregnancy Outcomes in Hidden Celiac Disease Autoimmunity

Abstract: INTRODUCTION: Untreated symptomatic celiac disease (CD) adversely affects female reproduction; however, the effect of hidden CD autoimmunity is uncertain. METHODS: We identified women who were not previously diagnosed with CD and tested positive for tissue transglutaminase and endomysial antibodies between 2006 and 2011 in a community-based retrospective cohort study. We evaluated (i) the rate of adverse pregnancy outcomes and medical complications of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Based on data from 4 cohort studies [ 29 , 32 , 33 , 46 ], among 5399 pregnancies of women with CD and 14,882,102 control pregnancies, there were 134 (2.5%) and 511,846 (3.4%) cases of preeclampsia, respectively. The association between CD pregnancies and the risk for preeclampsia was not statistically significant (RR 1.04, 95%CI 0.88-1.23).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on data from 4 cohort studies [ 29 , 32 , 33 , 46 ], among 5399 pregnancies of women with CD and 14,882,102 control pregnancies, there were 134 (2.5%) and 511,846 (3.4%) cases of preeclampsia, respectively. The association between CD pregnancies and the risk for preeclampsia was not statistically significant (RR 1.04, 95%CI 0.88-1.23).…”
Section: Resultsmentioning
confidence: 99%
“…In this analysis of 4 cohort studies [ 31 , 32 , 40 , 45 ], including 503 pregnancies with CD and 387,848 control pregnancies, the 5-min Apgar score was <7 in 2% (n=10) and in 1.7% (n=6483), respectively. There was no indication of an elevated risk for 5-min Apgar score <7 in the study group compared to the control group (RR 1.40, 95%CI 0.46-4.22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, high levels of serum coeliac autoantibodies have been associated with foetal growth restriction 57 . However, in another study an association was only reported between untreated coeliac seropositivity and small‐for‐gestational age in boys, but not with other adverse pregnancy outcomes 58 . Notwithstanding these partly controversial results, in addition to dietary counselling in general, specific focus on a strict gluten‐free diet could be beneficial for women with coeliac disease who are pregnant or planning pregnancy.…”
Section: Reproductive Healthmentioning
confidence: 99%
“…For attribution the title, original author(s), the publication source -NIHR Journals Library, and the DOI of the publication must be cited. 0 Reference Bizzaro et al 315 Feighery et al 316 Luft et al 320 Marai et al 409 Picceli et al 410 Sahin et al 411 412 Greco et al 310 Herraiz-Nicuesa et al 412 Hujoel et al 290 Kumar et al 415 Kumar et al 415 Kutteh et al 416 Celdir et al 422 Martinelli et al 423 Remes-Troche et al 413 Sarikaya et al 417 Shamaly et al 418 Sharshiner et al 419 Tiboni et al 420 Vanciková et al 401 Zahmatkeshan 421 Care. This is an Open Access publication distributed under the terms of the Creative Commons Attribution CC BY 4.0 licence, which permits unrestricted use, distribution, reproduction and adaption in any medium and for any purpose provided that it is properly attributed.…”
Section: Referencementioning
confidence: 99%